On Extreme Responsibility: What if Blackness/Whiteness could Go an Extra Mile? - Nyeck, S. N. (Virtuajus, 2024)
This essay sets out to investigate the contribution that black women thinkers and feminists bring to the debate over decolonization/decoloniality and to find out how much mileage can be covered with differential and oppositional politics only. Taking the Cameroonian novelist Calixthe Beyala’s intellectual and creative journeys as a feminist, writer, and activist for Black causes and identities, I argued the idea of decolonization as a break from something incompletely prepares us for a purposeful and inclusive activation of social transformation. Constructive decolonization, or a break from ontology toward some-Other, appears as a shock-event that reveals the crispation, contradiction and poverty of power in Africa’s racial experience